Potencialidades da utilização de taninos na conservação de forragens e nutrição de ruminantes-revisão - Oliveira, S. G. [UNESP]; Berchielli, Telma Teresinha [UNESP] (My University, 2007)
This review present a discussion abouth the tannins. The tannins are compounds that have the ability to bind other macromolecules, reducing their availability to animal metabolism. This characteristic can be benefic or deleterious, depending on the tannin concentration degree in the plant and its structure. Positive effects are mainly related with a better use of the dietary protein and an increased efficiency of microbial protein synthesis in the rumen. The use of tannins to reduce ruminal methane emission has been subject of current researches, firmly indicating a decrease of ruminal methanogenesis. However, many of these studies, carried out to evaluate the effects of tannins on forage fermentation and animal metabolism, are based on legume plants, so their results can not be surpassed to studies concerning tanniniferous grasses. By improving the characterization of the profile and reactivity of tannins in tanniniferous forages, such as some sorghum hybrids, as well as conducting experiments to demonstrate the effects of tannins on animal metabolism and performance, the real potential of forages with tannin will be enlightened.
Potentiality of tannins used in forages conservation and ruminant nutrition - A review
Keywords: Condensed tannin; Metabolism; Methane; Polyphenols; Ruminants; Animalia; Bovidae; Poaceae